Swings in commercial and residential land prices in the United States - Stephen D. Oliner; Joseph B. Nichols; Michael R. Mulhall (American Enterprise Institute (AEI), 2012)
We use a large dataset of land sales dating back to the mid-1990s to construct land price indexes for 23 MSAs in the United States and for the aggregate of those MSAs. The price indexes show a dramatic increase in both commercial and residential land prices over several years prior to their peak in 2006-07 and a steep descent since then. These fluctuations have exceeded those in well-known indexes of home prices and commercial real estate prices. Because those indexes price a bundle of land and structures, this comparison implies that land prices have been more volatile than structures prices over this period. This result is a key element of the land leverage hypothesis, which holds that home prices and commercial property prices will be more volatile, all else equal, in areas where land represents a larger share of real estate value.
Keywords: A; 330; Real estate; Housing Center: Research